CGIAR Initiative on One Health annual planning meeting, 24–25 April 2023 - Lore, Tezira A. (International Livestock Research Institute, 2023)
On 24–25 April 2023, the CGIAR Initiative on One Health held its annual planning meeting at the Addis Ababa campus of the International Livestock Research Institute, with some participants joining online via Microsoft Teams. The goal of the meeting was to bring together the work package leaders and core team to review the initiative’s achievements of 2022 and plan the research activities and deliverables for 2023. The specific objectives of the meeting were to: (1) review achievements of 2022 and discuss activities and deliverables planned for 2023 by each work package; (2) coordinate cross–work package activities including study locations, joint projects and collaboration with other initiatives; (3) discuss and reflect on communication, monitoring and evaluation, gender, scaling, staffing and budget; and (4) build the team and engage with partners in Ethiopia and the region at large.